A Review on Cyberloafing: The Effects of Social Platforms on Work Performance - Godlove Dismas Ngowella; Lamin Rene Loua; Suharnomo Suharnomo (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
Cyberloafing is a collection of work-related behaviours in which an employee engages in electronically-mediated activities, notably through the use of the internet, that are unrelated to their job duties. The development of communication technology has become a blessing in disguise for employees’ work performance, and over the years, organisations have tried to improve work-related activities that would have an impact on their employees’ work performance and also deal with how they cope with the usability of the internet. This paper aims to review and analyse cyberloafing with regards to the use of social platforms on work performance in previous studies conducted in Saudi Arabia. The findings demonstrate that increasing educational activities on an hourly basis has a favourable impact on work performance, whereas reducing time spent on social media networks increases time spent on work-related activities and hence increases work performance. Employers should create a balance between work and leisure time for their employees to ensure more productivity as technology makes people spend more time on their devices. Hence, work-leisure policies will be crucial in improving work performance and maintaining discipline during working hours.